Metasurface-based polarization color routers. (April 2023) - Zou, Xiujuan; Gong, Guangxing; Lin, Yu; Fu, Boyan; Wang, Shuming; Zhu, Shining; Wang, Zhenlin
Highlights: We experimentally demonstrate the metasurface-based polarization color router, which can simultaneously capture a Bayer-pattern (RGGB distribution) under white light with any polarization for color imaging and polarization detection. Differing from the forward design of metasurface, the metasurface is designed inversely using the global optimization algorithm (i.e. genetic algorithm) according to our design goal of sorting and guiding all incident light to different output ports. We ingeniously utilize the symmetry distribution of the nanostructures to realize the polarization response, which significantly simplifies the additional complexity of the polarization function design. In our color router, each unit cell of the metasurface performs both functions of focusing and spectrum sorting, which effectively solves the longstanding problems of low light throughput in most conventional color image sensors. Abstract: Polarization, an attribute of light, carries a lot of vital information independent of intensity and color content. Polarization imaging is very useful in applications including diffuse/specular component separation, material classification and reflectance estimation. Color routers applied in color imaging provide an efficient way to sort and guide different color lights to the corresponding output ports. Here, we report the design and experimental realization of a compact metasurface-based polarization color router. This color router shows a micron Bayer pattern (RGGB distribution) under the illumination of white light with any polarization. In addition, the green light intensity at the corresponding pixel changes regularly depending on the polarization light, illustrating the polarization color router can act as a polarizer at the same time. The measured light utilization efficiency of the polarization color router reaches a value of 88%. A correlation coefficient of 0.98, which is defined as the fitting effect between the measured and theoretical illuminating light polarization angles, was achieved. This device possesses the advantages of a lightweight, high light utilization efficiency and polarization-integrated detection functions, which could provide a new way for its applications in integrated CMOS image sensors.